Estudo dos mecanismos envolvidos na ação da pentoxifilina sobre a lesão hipocampal e deficits de memória induzidos por glutamato em ratos - Cunha, Geanne Matos de Andrade (1999)
The present work shows effects of pentoxifylline (ptx) on learning and memory in rats with hippocampal lesion induced by glutamate (glu). The animais (male Wistar rats, 200- 250g) were submitted to stereotaxic surgery and injected in the hippocampus (CAI, CA3) with glu at doses of 24, 48, 96 and 192 pg. After 7 days, animais were tested in the open-field to evaluate locomotor activity and submitted to memory tests (passive avoidance, elevated T maze, and water maze). Twenty-four hours later, animais were sacrificed for histopathological studies. The results show no significant lesion in the saline and glu (24 and 48 pg) groups. However, moderate to severe lesions were observed at higher glu doses (96 and 192 pg). Increased locomotor activity after glu as compared to Controls was observed only with the dose of 192 pg (saline: 14,82 ± 2,59, glul92: 31,10 ± 6,50 squares). In the passive avoidance test the groups treated with glu 48, 96 and 192 pg, showed memory deficits, in early memory (saline: 200,43 ± 52,09; glu24: 210,20 ± 44,77; glu48: 27,61 ± 9,89; glu96: 64,46 ± 31,93; glu 192: 140,29 ± 40,76s), as well as in the late memory (saline: 252,57 ± 31,78; glu24: 273,70 ± 22,27; glu48: 44,35 ± 32,21; glu96: 29,39 ± 14,54, glul92: 140,29 ± 40,76s). In the elevated T-maze, animais treated with glu at higher doses showed a lower performance as compared to Controls. Analyses of memory retention in the water maze showed defict in spatial memory (saline: 10,95 ± 3,56, glu96: 26,89 ± 3,97, glu 192: 32,79 ± 4,78s). Ptx at lOOmg/kg, protected animais against glu(96 pg)-induced lesion. Besides ptx did not alter locomotion activity, but when injected in lesioned animais an increased locomotor activity was observed. In the elevated T-maze, ptx-treated animais presented a better performance, decreased the deficits produced by glu (Avoidance 3- saline: 188,51 ± 26,66, glu96: 144,76 ± 33,74, ptxlOO: 293,55 ± 6,44, ptx200: 185,25 ± 32,45, ptxlOO+glu: 237,42 ± 29,06, ptx200+glu: 168,32 ± 41,07s) (KW, p<0,05). In the passive avoidance test, ptx reduced the amnesic effects produced by glu lesion (late memory- ptx50+glu: 300,00 ± 0,00, ptxlOO+glu: 176,67 ± 34,32; ptx200+glu: 221,19 ± 35,41s (KW, p<0,05). In the water maze test, ptx was also effective as far as learning acquisition is concerned (ptx200+glu: 12,96 ± l,84s). The glu lesion caused a decrease in cAMP leveis which was reverted by ptx (saline: 0,966, glu: 0,186, ptxlOO+glu: 1,060 pmol/mg protein. Pre-treatment with CPA, Al, adenosine agonist or with thalidomide (TNF-a inhibitor) did not reversed or potentiated respectively ptx effects on rat memory. A central cholinergic (muscarinic) effect of ptx, was also demonstrated by the potentiation of oxotremorine (muscarinic agonist) induced tremores by ptx (oxo: 1,53 ± 0,33, ptx50 + oxo: 5,30 ± 1,23, ptxlOO+oxo: 8,47 ± 0,61 scores/30min). Besides, ptx decreased muscarinic receptor number (saline: 181,71, ptxlOO: 132,74 ± 11,80 fmoles/mg protein) on brain hippocampus and decreased AChE activity. An increase and decrease respectively nitrite/nitrate leveis were detected after glu and ptx+glu groups (saline: 5,24 ± 0,82, glu96 9,22 ± 1,20, ptxlOO+glu: 5,98 ± 0,46 pM). It is possible that, the citoprotector effect demonstrated by ptx in the present work is related to the antiinflammatory effect of the drug, through the inhibition of the cytokines production such as TNF-a and the inhibition of reactive oxygen species produced by ptx. Besides, the increased in cAMP leveis produced by ptx associated to its central cholinergic action could contribute to the reduction of memory deficits detected after glutamate induced hippocampal lesion in rats.